(untitled) (Minerva, 2017)
This paper offers an evaluation of the “Apologia against Pliny” in the eighth volume (1781), entirely devoted to Columella, in Historia Li-teraria de España, an ambitious work by the two friars Rodríguez Mohedano. By means of a close reading of the “Apologia”, the reasons presented by the authors are here established and considered. Furthermore, the argument of ‘Italy versus Spain’ competition is examined in its context; and a particular topic of controversy between Columella and Pliny (Persica poma) is analyzed. Ultimately the paper shows, in a quite complete way, the method of Mohedanos’ work, their scholarship and intellectual attitude.